The Influence Of Destination Image, Smart Tourism Technology, Environmental Concern, And Destination Innovation On Experience Quality, Tourist Satisfaction, And Tourist Loyalty In Wonosobo - Muchammad Syafiq Murtadho Syafiq; Sarwoto (Al-Kharaj: Journal of Islamic Economic and Business, 2026)
The purpose of this study is to measure the relationship between Destination Image, Smart Tourism Technology, Environmental Concern, Destination Innovation, Experience Quality, Tourist Satisfaction, and Tourist Loyalty. A quantitative approach was applied by collecting data from local tourists visiting tourist destinations in Wonosobo Regency. Data collection was conducted online by sending a questionnaire link to respondents. Structural Equation Modeling (SEM) was used for analysis in this study. The results showed that Destination Image, Smart Tourism Technology, Environmental Concern, Destination Innovation, Experience Quality, and Tourist Satisfaction have a significant impact on Tourist Loyalty to revisit tourist destinations in Wonosobo Regency. This study is expected to provide guidance to destination marketing managers to make their destinations sustainable by fostering visitor loyalty. To achieve this goal, The destination is suggested to leverage Destination Image, Smart Tourism Technology, environmentally friendly destinations, and innovation to enhance the quality of experiences and customer satisfaction, encouraging tourists to return.